2014
DOI: 10.1080/15459624.2013.862592
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors That Influence Protective Glove Use Among Automotive Spray Painters

Abstract: Dermal contact with isocyanate-based coatings may lead to systemic respiratory sensitization. The most common isocyanates found in sprayed automotive coatings are monomeric and oligomeric 1,6-hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI). Most spray painters use thin (4–5 mil) latex gloves that are not effective at preventing dermal exposures when spraying isocyanate paints. Personal interviews with collision repair industry personnel and focus groups with spray painters were held to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thicker gloves as in PVC gloves would decrease workers' manual dexterity and cause fatigue due to the higher muscle resistance. Thicker gloves can affect the breathability and may cause more sweat production due to a humid environment [30]. Neoprene gloves are more elastic than the PVC gloves which allows the workers to control hand movement and have less fatigue [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thicker gloves as in PVC gloves would decrease workers' manual dexterity and cause fatigue due to the higher muscle resistance. Thicker gloves can affect the breathability and may cause more sweat production due to a humid environment [30]. Neoprene gloves are more elastic than the PVC gloves which allows the workers to control hand movement and have less fatigue [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sparer, et al [21] also stated that isocyanate when used as catalysts, hardeners in two-part polyurethane in the final "clear coat" is recognized as being of principal concern and that when these products are sprayed, the aerosolised liquids can create a significant inhalation hazard for airborne isocyanate. Though spray painters were familiar with the health hazards related to working with isocyanate paints, they may not know that the nonusage of hand gloves would lead to dermal exposure to isocyanate, which could contribute to occupational asthma as noted by Ceballos, et al [24]. Kamal and Malik [14] found that spray painting occupation had significantly higher mean corpuscle volume (MCV) and increased MCV may indicate the side effects on liver and that of pernicious anaemia [25] which may be due to an aromatic exposure in an occupational group.…”
Section: Discussionmentioning
confidence: 99%